SWOT -AHP AS A METHOD OF PUBLIC SERVICE STRATEGY - Juharni Juharni; Syamsul Bahri; Delly Mustafa; Sitti Hardiyanti Arhas (Sosiohumaniora, 2023)
SWOT-AHP helps companies to develop and plan strategic alternatives to overcome all the challenges faced. The purpose of this study is to determine the public service strategy of the Makassar Laboratory Center. This research is a quantitative research, using the SWOT-AHP approach to determine the right strategy in improving organizational performance. Data is collected from the documentation results and then analyzed according to SWOT-AHP stages.  The results of data processing show that in the item of strength, having an international standard TB lab is the most dominant strength possessed by BBLK Makassar, in the item of weakness, the biggest weakness is the organizational culture that still tends to be negative (rigid, individual, passive, lack of empathy in providing services, so efforts need to be made for the organization to carry out public services based on public excellent. While the most dominant opportunity to be utilized is information technology support, while the biggest threat faced by BBLK Makassar is the entry of foreign investors in laboratory services that have more sophisticated systems and equipment (the threat of global competition in the AFTA era). After the SWOT-AHP analysis, 4 strategies emerged, namely: increasing the promotion and technology-based information services, building an integrated information technology system, improving the quality and quantity of human resources, and maximizing tool utilization by adding new types of examinations.